Pulsed corona discharge oxidation of aqueous carbamazepine micropollutant; Environmental Technology; Vol. 37, iss. 16 - Ajo P. Petri; Krzymyk E. Ewelina; Preis S. Sergei; Kornev Ya. I. Yakov Ivanovich; Kronberg L. Leif; Louhi-Kultanen M. Marjatta (2016, 2016)
Title screen